Visuo-haptic transfer for object recognition in children with peripheral visual impairment. (January 2021) - Purpura, Giulia; Febbrini Del Magro, Elena; Caputo, Roberto; Cioni, Giovanni; Tinelli, Francesca
Highlights: Visual disorder impacts the transfer of visual information during haptic object manipulation. In low-vision children, multisensory processes do not facilitate the recognition of objects. Haptic and visual representations of objects have an independent maturation. Abstract: It is well known how early visual experience is critical for the development of multisensory processing abilities, and for this reason an early vision impairment could hinder the transfer of different sensory information during the exploration and recognition of the surrounding environment. Recently, we verified that visuo-haptic transfer for object recognition emerges early in typically developing children but matures slowly during the school-age period. Subsequently we verified the presence of a slower trend of development in unisensory and multisensory skills in children with early abnormal motor and sensory experiences due to brain lesions. Now, we investigated unimodal visual information, unimodal haptic information and visuo-haptic information transfer in children with a diagnosis of low-vision, due to congenital visual impairment. Unimodal and bimodal processes for object recognition were explored in 11 children with low-vision and the results were matched with those of 22 controls. Participants were tested using a clinical protocol involving visual exploration of black-and-white photographs of common objects, haptic exploration of real objects and visuo-haptic transfer of these two types of information. Results show a normal development in haptic unisensory processing in children with low vision and a significant difference in multisensory transfer between the two groups. In children with visual impairment, multisensory processes do not facilitate the recognition of common objects as in typical children, probably because early visual impairment may impact the cross-sensory calibration of vision and touch.